2023
DOI: 10.3390/microorganisms11051343
|View full text |Cite
|
Sign up to set email alerts
|

Localization of C Cycle Enzymes in Arable and Forest Phaeozems within Levels of Soil Microstructure

Abstract: Soil microbial and enzyme activities are closely related to the spatial variability of soil environmental conditions at the microscale (μm-mm). The origin and localization of the enzymes are somewhat neglected when the measured activity is used to evaluate specific soil functions. The activity of four hydrolytic enzymes (β-glucosidase, Cellobiohydrolase, Chitinase, Xylanase) and microbial diversity based on community-level physiological profiling were determined in samples of arable and native Phaeozems with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Changes in the three altitudinal gradients have a strong influence on the bacterial phylum, which is relatively abundant in soil microorganisms (Proteobacteria, Firmicutes, Chloroflexi, and Gemmatimonadota) and slope orientation had a significant effect on Actinobacteriota and Thermoleophilia in the bacterial community. He's (2023) showed that altitudinal gradients are associated with changes in different environmental factors that trigger different habitat-specific patterns and have different effects on different microbial communities [24][25][26]. Zhou's (2019) showed that Actinobacteriota, an oligotrophic taxon with strong metabolism and DNA repair mechanisms even at low temperatures, prefers nutrient-poor alkaline environments [21,27].…”
Section: Structural Composition Of Soil Microbial Communities At Diff...mentioning
confidence: 99%
“…Changes in the three altitudinal gradients have a strong influence on the bacterial phylum, which is relatively abundant in soil microorganisms (Proteobacteria, Firmicutes, Chloroflexi, and Gemmatimonadota) and slope orientation had a significant effect on Actinobacteriota and Thermoleophilia in the bacterial community. He's (2023) showed that altitudinal gradients are associated with changes in different environmental factors that trigger different habitat-specific patterns and have different effects on different microbial communities [24][25][26]. Zhou's (2019) showed that Actinobacteriota, an oligotrophic taxon with strong metabolism and DNA repair mechanisms even at low temperatures, prefers nutrient-poor alkaline environments [21,27].…”
Section: Structural Composition Of Soil Microbial Communities At Diff...mentioning
confidence: 99%